Hybrid Source-Receiver Geometry for Short-Spread Layout in 2D Seismic Reflection Acquisition - Khairul Arifin Mohd Noh, Zuhar Zahir Tuan Harith, Abdul Halim Ab, . (2015)
A seismic spread refers to the location of the source with respect to the receivers associated with that specific source. In land 2D seismic reflection acquisitions, survey coverage (i.e. distance and depth)is the main issue since the numbers of active geophone are limited.